Alunite spectral features and mineral chemistry of the Zijinshan-Dafanshan lithocap in SE China: Implications for mineral exploration - Sun, Yandong; Xie, Guiqing; Chen, Jing (Acta geochimica, 2023)
Lithocaps are composed of silicic and advanced argillic altered rocks, and represent an important target for porphyry-epithermal Cu-Au exploration. Previous studies showed that integrating alunite spectral and composition with lithocap whole-rock geochemistry can effectively aid exploration for concealed Cu-Au mineralization. The Zijinshan Cu-Au and Dafanshan alunite deposits are located in the Coastal Volcanic Belt in SE China, where alunite is an indicator of hypogene mineralization and alteration. Detailed mineralogical studies of alunite from these two deposits were performed with short-wavelength infrared spectroscopy (SWIR), whole-rock geochemistry and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). For Zijinshan, wavelength variation of the SWIR alunite absorption peak at 1480 nm is proportional to the whole-rock Na/(Na + K) molar ratio of alunite-bearing samples. Different percentage of alunite and mineral assemblages in the lithocap samples would both affect the wavelength of the SWIR alunite absorption peak at 1480 nm. We suggest that the alunite Ba-Bi contents and the whole-rock Nb/La value (of alunite-bearing rocks) are reliable vectoring tools for detecting magmatic-hydrothermal mineralization center in the district. Comparing the alunite SWIR spectral and mineral geochemical features and whole-rock geochemistry of alunite-bearing rocks between the Zijinshan and Dafanshan deposits, Au–Ag mineralization may be concealed at depth in northwestern Dafanshan.